Manipulation, Socio-psychological Impact of False Promises of Marriage to Shona Women in Selected Shona Novels - Caroline Chiumburu; Davie E Mutasa (Universitas Sanata Dharma, 2025)
This article discusses the victimisation of women who were promised false marriage by men in selected Shona literature. It unravels why women fall prey and quizzes why men manipulate the marriage institution for personal satisfaction. The article utilises the feminist literary theory to interrogate two novels, Makudo Ndomamwe (Men are All the Same) (2004) by R. Makaya and Imbwa Nyoro (1982) (Innocent Ones are Often Guilty) by R. M. Mumvuma. Patriarchy as a major tenet of the feminist literary theory is used as a key guide in the interrogation of female manipulation after they are promised marriage in these novels. A qualitative research methodology utilizing a textual analysis approach is adopted. Additionally, scholarly views are gathered through questionnaires to draw their insights on the interplay of the patriarchal system in manipulating marriage proposals by men among the Shona people. The study discovers that women in the novels succumb to suppression. They are suffering from sexual objectification, violence and male centeredness, female silencing, male domination and control. This transpires because among the Shona, marriage accords women a perceived social status and it acquires them lifelong companionship and attains them much more respect in the community where they were born. The article concludes by providing recommended solutions to women and the society in preventing and raising awareness on the manipulation of the marriage proposals.